Emerging aspects of nanotoxicology in health and disease: From agriculture and food sector to cancer therapeutics. (May 2016) - Piperigkou, Zoi; Karamanou, Konstantina; Engin, Ayse Basak; Gialeli, Chrysostomi; Docea, Anca Oana; Vynios, Demitrios H.; Pavão, Mauro S.G.; Golokhvast, Kirill S.; Shtilman, Mikhail I.; Argiris, Athanassios; Shishatskaya, Ekaterina; Tsatsakis, Aristidis M.
Abstract: Nanotechnology is an evolving scientific field that has allowed the manufacturing of materials with novel physicochemical and biological properties, offering a wide spectrum of potential applications. Properties of nanoparticles that contribute to their usefulness include their markedly increased surface area in relation to mass, surface reactivity and insolubility, ability to agglomerate or change size in different media and enhanced endurance over conventional-scale substance. Here, we review nanoparticle classification and their emerging applications in several fields; from active food packaging to drug delivery and cancer research. Nanotechnology has exciting therapeutic applications, including novel drug delivery for the treatment of cancer. Additionally, we discuss that exposure to nanostructures incorporated to polymer composites, may result in potential human health risks. Therefore, the knowledge of processes, including absorption, distribution, metabolism and excretion, as well as careful toxicological assessment is critical in order to determine the effects of nanomaterials in humans and other biological systems. Expanding the knowledge of nanoparticle toxicity will facilitate designing of safer nanocomposites and their application in a beneficial manner. Highlights: Applications of nanotechnology in food and pharma production is an emerging field. According to European Commission, immunotoxicological assessments of nanoparticles are necessary. We reappraised the cross-roads of cellular and immunological mechanisms of nanoparticle actions. Interaction of nano-bio interfaces affects the utilization of nanomaterials in clinical applications and food industry. Nanoparticle toxicity was debated for the safer design and application of nanomaterials.